Hepatocellular Carcinoma in Cirrhotic Versus Noncirrhotic Livers: Clinicomorphologic Findings and Prognostic Factors - Karaoğullarından, Ümit; Üsküdar, Oğuz; Odabaş, Emre; Ak, Numan; Kuran, Sedef (Turkish Journal of Gastroenterology, 2023)
Background: Hepatocellular carcinoma mostly develops in a cirrhotic (80%) background. The clinical features of cirrhotic hepatocellular carcinoma and non-cirrhotic hepatocellular carcinoma also differ. We aimed to determine the clinicopathologic features, tumor characteristics, treatment options, and overall survival after diagnosing hepatocellular carcinoma and prognostic factors effective on survival of hepatocellular carcinoma developing in cirrhotic and non-cirrhotic conditions. Methods: In our study, 220 patients aged over 18 years who were histologically diagnosed as having hepatocellular carcinoma were included. The patients were divided into 2 groups as cirrhotic and non-cirrhotic. Results: When the tumor morphologies were examined in our study, it was observed that they were mostly solitary in both groups. Cirrhotic hepatocellular carcinomas had significantly higher rates of invasion than the non-cirrhotic group (35.3% vs. 20.3%, respectively) (P <.05). The survival rate was found to be better in the non-cirrhotic group (17.5 months vs. 11.5 months) (P <.05). Age, maximal tumor diameter, and morphologically infiltrative tumor character were found to be independent risk factors affecting survival in patients with cirrhosis. Portal vein invasion, alfa-fetoprotein, and the absence of an underlying risk factor in the etiology were observed as independent risk factors affecting survival in patients with non-cirrhosis. Conclusion: Cirrhotic hepatocellular carcinoma and non-cirrhotic hepatocellular carcinoma had different clinicopathologic features and risk factors. We analyzed that treatment choice trends were different between the 2 groups. We also observed that the factors that affected survival were different between the 2 groups. Cite this article as: Karaoğullarından Ü, Üsküdar O, Odabaş E, Ak N, Kuran S. Hepatocellular carcinoma in cirrhotic versus non-cirrhotic livers: Clinicomorphologic findings and prognostic factors. Turk J Gastroenterol. 2023;34(3):262-269.